Case Report: Anal canal duplication associated with anorectal stenosis—A rare presentation - Zheng, Zhen; Xiao, Dong; Wang, Junxiang; Xu, Haozhong; Mao, Jianxiong; Wang, Xiuliang (Frontiers in Pediatrics, 2022)
Anal canal duplication (ACD) is a rare alimentary tract malformation, defined as extra anal orifices located at 6 o’clock in the lithotomy position. Only 110 cases have been reported. This study aims to contribute with two infant cases, one of them presenting with megacolon, which has never been described before.